2020
DOI: 10.1021/jasms.0c00067
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Labeling/Mass Spectrometry of Monoclonal Antibodies with Diethylpyrocarbonate: Reaction Kinetics for Ensuring Protein Structural Integrity

Abstract: Diethylpyrocarbonate (DEPC)-based covalent labeling together with mass spectrometry is a promising tool for the higher-order structural analysis of antibody therapeutics. Reliable information about antibody higher-order structure can be obtained, though, only when the protein's structural integrity is preserved during labeling. In this work, we have evaluated the applicability of DEPC reaction kinetics for ensuring the structural integrity of monoclonal antibodies (mAbs) during labeling. By monitoring the modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…Labeling was conducted at a DEPC:protein molar ratio of 4:1 at 37 °C for 5 min. We have found that a 5 min reaction a 4:1 molar ratio leads to sufficient labeling of antibodies without perturbing the protein’s structure . Imidazole was then added at a 1:50 DEPC:imidazole molar ratio to quench the reaction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Labeling was conducted at a DEPC:protein molar ratio of 4:1 at 37 °C for 5 min. We have found that a 5 min reaction a 4:1 molar ratio leads to sufficient labeling of antibodies without perturbing the protein’s structure . Imidazole was then added at a 1:50 DEPC:imidazole molar ratio to quench the reaction.…”
Section: Methodsmentioning
confidence: 99%
“…We have found that a 5 min reaction a 4:1 molar ratio leads to sufficient labeling of antibodies without perturbing the protein's structure. 30 Imidazole was then added at a 1:50 DEPC:imidazole molar ratio to quench the reaction. For each stress conditions, at least three replicates were performed on the rituximab samples.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Footprinting techniques such as covalent labeling, HDX, and FPOP provide a direct and granular assessment of antibody stabilities . Covalent labeling measurements can reveal subtle changes to HOS, structural integrity, and antigen interactions . HDX exchange methodologies are well established for the assessment of mAb stability and are increasingly used to determine elements of biotherapeutic HOS. , FPOP methods have also demonstrated their general utility in the characterization of mAb HOS , and have specifically excelled in the area of epitope mapping. , …”
Section: Biotherapeuticsmentioning
confidence: 99%
“…Footprinting MS. Footprinting techniques such as covalent labeling, HDX, and FPOP provide a direct and granular assessment of antibody stabilities. 331 Covalent labeling measurements can reveal subtle changes to HOS, 332 structural integrity, 333 and antigen interactions. 162 HDX exchange methodologies are well established for the assessment of mAb stability 334 and are increasingly used to determine elements of biotherapeutic HOS.…”
Section: Standard Andmentioning
confidence: 99%
“…Another CL reagent that has been used extensively to study protein interactions is diethylpyrocarbonate (DEPC). Unlike FPOP, which requires a special experiment setup, DEPC can simply be added to solution whereupon it labels nucleophilic residues such as Cys, Lys, His, Ser, Thr, and Tyr. DEPC reacts with protein side chains on the seconds to minutes time scale and is therefore affected by protein dynamics in a different manner than FPOP.…”
Section: Introductionmentioning
confidence: 99%